Effects of cold exposure on behavioral and electrophysiological parameters related with hippocampal function in rats - Elmarzouki, Hajar; Aboussaleh, Youssef; Bitiktas, Soner; Suer, Cem; Artis, A. Seda; Dolu, Nazan; Ahami, Ahmed (Frontiers in Cellular Neuroscience, 2014)
Aim: Behavioral and mental changes may occur in people exposed to cold stress by decreasing their work efficiency and their mental capacity while increasing the number of accidents on the job site. The goal of this study was to explore the effect of cold stress in spatial learning performance excitability and LTP. Materials and Methods: Three to four month old rats were randomly divided into four groups to form a control group and a cold stress group for each sex. The groups of cold stressed animals were placed in a cold room ambient temperature of 4°C for 2 h day. Adrenal glands and body weight (g) were recorded in control and stressed rats during the cold exposure. Spatial learning (acquisition phase) and memory (probe trial) were tested in the Morris water maze (MWM) immediately after daily exposure. Latency to locate the hidden platform, distance moved (DM), mean distance to platform, swim speed (SS) and time spent in the platform quadrant were compared between genders and treatments. Field potential recordings were made, under urethane anesthesia, from the dentate gyrus (DG) granule-cell layer, with stimulation of the medial perforant pathway 2 h after the probe trial. This study examined spatial memory as measured by MWM performance and hippocampal long-term potentiation (LTP) in the DG after exposure to cold in a repeated stress condition for 2 h/day for 5 days. Results: The cold-exposed female rats needed less time to find the hidden platform on day 1 (43.0 ± 13.9 s vs. 63.2 ± 13.2 s), day 2 (18.2 ± 8.4 s vs. 40.9 ± 12.2 s) and on day 4 (8.0 ± 2.1 s vs. 17.2 ± 7.0 s) while cold-exposed male rats showed a decreased escape latency (EL) on day 1 only (37.3 ± 12.5 s vs. 75.4 ± 13.1 s). Cold-exposed male rats spent less time in the target quadrant (30.08 ± 6.11%) than the control male rats (37.33 ± 8.89%). Two hour cold exposure decreased population spike (PS) potentiation during both induction (218.3 ± 21.6 vs. 304.5 ± 18.8%) and maintenance intervals (193.9 ± 24.5 vs. 276.6 ± 25.4%) in male rats. Meanwhile cold exposure did not affect the body weight (C: 221 ± 2.5 vs. S: 222 ± 1.7) but it impacts the adrenal gland relative weight (S: 27.1 ± 1.8 mg vs. C: 26.2 ± 1.4 mg). Conclusion: Overall, the results show that repeated cold exposure can selectively improve spatial learning in adult female rats, but impaired retention memory for platform location in male rats. It is possible that impaired LTP underlies some of the impaired retention memory caused by cold exposure in the male rats.